Prediction of financial distress in foreign exchange banking firms using risk analysis, good corporate governance, earnings, and capital - Ali Machsum Harahap (The Indonesian Accounting Review, 2015)
The main role of a bank is to collect funds from those who have surplus funds and distribute them to those who have a shortage of funds with the purpose to make benefit from such activity. However, this activity would bring problem when the bank is underfunded or experiencing financial distress due to the customers inability to repay the funds. This study aims to test whether the ratio of non-performing loans (NPL), Loan to Deposit Ratio (LDR), Good Corporate Governance (GCG), and Return on Assets (ROA), Net Interest Margin (NIM) and the Capital Adequacy Ratio (CAR) can be used to predict financial distress in Foreign Exchange Banking Firms in the period 2009-2012. The initial samples in this study are 35 Foreign Exchange Banks, but there are only 16 Foreign Exchange Banks that meet the criteria. The sampling technique used is purposive sampling method and the data used in this study is a secondary data by looking at the financial statements and the related statements of GCG of the Banks. The test equipment used to test the hypo-thesis is logistic regression. These results indicate that the ratio of ROA and NIM can be used to predict financial distress in Foreign Exchange Banks because ROA and NIM have significance value below 0.05 (5%). While the ratio of NPL, LDR, GCG and CAR cannot be used to predict financial distress in Foreign Exchange Banks because NPL, LDR, GCG, and CAR have significance value above 0.05 (5%).